Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

I need this ASAP!!!!!!

I Need This ASAP class=

Sagot :

Answer:

(x, y) = (1, -9)

Step-by-step explanation:

y = -9x

-8x-6y = 46

By substituting the value of y (first equation) into the second equation, we get,

-8x - 6*(-9x) = 46

-8x + 54x = 46

46x = 46

x = 1.

So, y = -9